Multidirectional Effects of Tormentil Extract on Hemostasis in Experimental Diabetes - Marcinczyk, Natalia; Gołaszewska, Agata; Gromotowicz-Poplawska, Anna; Misztal, Tomasz; Strawa, Jakub; Tomczyk, Michał; Kasacka, Irena; Chabielska, Ewa (Frontiers in Pharmacology, 2021)
In our previous study, we showed that ellagitannin- and procyanidin-rich tormentil extract (TE) decreased experimental arterial thrombosis in normoglycemic rats through platelet inhibition. TE also slightly increased coagulation and attenuated fibrinolysis; however, these effects did not nullify the antithrombotic effect of TE. The present study aimed to assess whether TE exerts antithrombotic activity in streptozotocin (STZ)-induced diabetes, which is characterized by pre-existing increased coagulation and impaired fibrinolysis, in vivo and ex vivo thrombosis assays. TE (100, 200, or 400 mg/kg, p. o.) was administered for 14 days to STZ-induced diabetic rats and mice. TE at 100 mg/kg dose decreased the thrombus area in the mice model of laser-induced thrombosis through its potent antiplatelet effect. However, TE at 200 mg/kg dose increased thrombus weight in electrically induced arterial thrombosis in rats. The prothrombotic effect could be due to increased coagulation and attenuated fibrinolysis. TE at 400 mg/kg dose also improved vascular functions, which was mainly reflected as an increase in the arterial blood flow, bleeding time prolongation, and thickening of the arterial wall. However, TE at 400 mg/kg dose did not exert antithrombotic effect. Summarizing, the present results show that TE may exert multidirectional effects on hemostasis in STZ-induced diabetic rats and mice. TE inhibited platelet activity and improved endothelial functions, but it also showed unfavorable effects by increasing the activity of the coagulation system and by inhibiting fibrinolysis. These contrasting effects could be the reason for model-specific influence of TE on the thrombotic process in STZ-induced diabetes.